Interprofessional collaboration in the breast cancer unit: how do healthcare workers see it? - Dea Anita Ariani Kurniasih; Elsa Pudji Setiawati; Ivan Surya Pradipta; Anas Subarnas (BMC, 2022)
Abstract Background Interprofessional collaboration has an important role in health care for breast cancer patients who are undergoing treatment at the hospital. Interprofessional collaboration has been reported to provide significant benefits for patients. However, qualitative research on interprofessional collaboration in the breast cancer department is rarely done, therefore, a study was conducted to determine the perception of health practitioners about interprofessional collaboration in the breast care unit at a referral centre hospital in West Java, Indonesia. Methods A qualitative study was carried out using in-depth interviews and focus group discussions (FGDs) with 15 healthcare personnel using total sampling. Participants were chosen among healthcare professionals who treat and in charge for outpatient breast cancer, but were not resident physicians. The FGD approach was used for nurses and pharmacists, and interviews were used for oncologists. The audio recordings of all interviews and FGDs were transcribed verbatim and evaluated using thematic analysis. Result The findings were categorized into two categories to obtain health care workers' perspectives on interprofessional collaboration: (1) impediment factors: personality, lack of leadership, seniority, healthcare workers with double positions, the need for a clinical meeting, hospital bureaucracy, national health insurance implementation, issues with patients, hospital infrastructure, and evaluation and synchronisation; (2) existing supportive elements: effective cooperation, effective communication, clear job description, interpersonal relationships, Standard Operational Procedure (SOP) for cancer therapy, legality for inter-discipline cancer team, professional responsibility, integrated clinical pathway, patient centred care, and comprehensive health services. Conclusions Interprofessional collaboration was seen positively by the respondents. However, there are several hurdles that must be overcome to apply interprofessional collaboration works effectively. The findings of this study can be used to build interprofessional collaborations targeted at enhancing quality health care in breast cancer units.